#TITLE_ALTERNATIVE# - MARDHIKA (NIM 12303023) pembimbing : Dr.Eng. Ir. T. A. Sanny, M.Sc, ZAIN
Conventionally, amplitude variation offset analysis has been applied at prestack section for reservoir characterization process. Reliability of amplitude variation offset analysis is proven for geological condition with simple structure otherwise for complex geological condition there is still have problem whether amplitude variation offset analysis can be applied relating with any problems that happened along imaging process which can distorte and damage the amplitude signal. So, a better method than conventional method is needed. One of the method is using a prestack section of partial crs stack method. In this final project, that two method will be compared to see how good both section can be used for amplitude analysis. Conventional and partial crs stack method is applied to synthetic data modeling of acustic waves through the marmousi2 model and the half graben model. At model, there is a gas sand reservoir included with both stratigraphic trap and structural trap. The data will be processed until prestack time migration by both method. Kirchhoff migration algorithm are used in this process. From the comparison prestack section between two methods.the results of partial crs stack method can be used for amplitude variation offset analysis at top and bottom of gas reservoir sand